2023
DOI: 10.3934/jimo.2021177
|View full text |Cite
|
Sign up to set email alerts
|

Project portfolio selection based on multi-project synergy

Abstract: <p style='text-indent:20px;'>To date, the selection of a project portfolio that maximises the decision-making outcome remains essential. However, existing research on project synergy has mainly focused on two projects, while there are multiple projects in some cases. Two kinds of synergies among multiple projects are proposed. First, multiple projects must be selected together, in order to produce synergy. Second, some projects depend on synergy with other projects, leading to a synergetic increase in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(65 reference statements)
0
5
0
3
Order By: Relevance
“…Wilderich (2012) contributed to the PPM by combining project integration with the holistic view of managing PP. Wang et al (2021b) found that, without intentional intervention on the part of PP leadership, risk management processes and practices executed by individual projects may not support optimal risk management at the PP level. As a result, PPM is required to manage risks and opportunities across projects.…”
Section: Ppmmentioning
confidence: 97%
See 2 more Smart Citations
“…Wilderich (2012) contributed to the PPM by combining project integration with the holistic view of managing PP. Wang et al (2021b) found that, without intentional intervention on the part of PP leadership, risk management processes and practices executed by individual projects may not support optimal risk management at the PP level. As a result, PPM is required to manage risks and opportunities across projects.…”
Section: Ppmmentioning
confidence: 97%
“…These studies are important because they explained what PPM could do. Some other contributions to the related literature stress the importance of PPM in prioritizing Wu et al (2011), selecting ECAM 31,2 (Wang et al, 2021b) and integrating projects (Wilderich, 2012). Wu et al (2011) considered the project prioritization part of the PPM process a key factor for success.…”
Section: Ppmmentioning
confidence: 99%
See 1 more Smart Citation
“…Projeler arasındaki sinerji, belirli bir kaynağın veya teknolojinin projeler arasında paylaşılması gibi projeler arasındaki etkileşimden kaynaklanabilir. Sinerji olumlu ve olumsuz olarak iki kategoriye ayrılabilir, buna göre olumlu sinerji projenin beklenen sonucunu artırırken, olumsuz sinerji projenin beklenen sonucunu azaltır [24]. Mevcut araştırmalardaki projelerin sinerjisi, fayda sinerjisi, kaynak sinerjisi ve teknoloji sinerjisi olarak sınıflandırılabilir [24].…”
Section: Introductionunclassified
“…However, a PP typically consists of several projects, programs and subsidiary portfolios according to the Project Management Institute (PMI). These components make projects share or compete for limited resources, and significant interactions exist among these projects in terms of resources, technology and benefits (Killen and Kjaer, 2012; Wang et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%